2023
DOI: 10.1101/2023.10.11.561932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping chromatin state and transcriptional response in CIC-DUX4 undifferentiated round cell sarcoma

Nicholas J. Thomas,
Cuyler Luck,
Nicole Shlimon
et al.

Abstract: CIC-DUX4 is a rare and understudied transcription factor fusion oncoprotein. CIC-DUX4 co-opts native gene targets to drive a lethal form of human sarcoma. The molecular underpinnings that lead to oncogenic reprograming and CIC-DUX4 sarcomagenesis remain largely undefined. Through an integrative ChIP and RNA-Seq analysis using patient-derived CIC-DUX4 cells, we define CIC-DUX4 mediated chromatin states and function. We show that CIC-DUX4 primarily localizes to proximal and distal cis-regulatory elements where i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…One interesting observation that is consistent with other findings is that CIC::DUX4 localizes and binds to GGAA-motif sequences on DNA (Kim et al, 2022;Bakaric et al, 2024). These findings indicate that WT CIC and CIC::DUX4 (among other CIC rearrangements) may regulate gene expression through non-consensus (non TGAATGAA-like) like motifs (Thomas et al, 2023). Future studies aimed at identifying and differentiating which genes are regulated by CIC::DUX4 at TGAATGAA versus GGAA-like DNAmotifs is highly warranted.…”
Section: Murine Modelssupporting
confidence: 83%
See 1 more Smart Citation
“…One interesting observation that is consistent with other findings is that CIC::DUX4 localizes and binds to GGAA-motif sequences on DNA (Kim et al, 2022;Bakaric et al, 2024). These findings indicate that WT CIC and CIC::DUX4 (among other CIC rearrangements) may regulate gene expression through non-consensus (non TGAATGAA-like) like motifs (Thomas et al, 2023). Future studies aimed at identifying and differentiating which genes are regulated by CIC::DUX4 at TGAATGAA versus GGAA-like DNAmotifs is highly warranted.…”
Section: Murine Modelssupporting
confidence: 83%
“…Thus, it is reasonable to conceive that CIC::DUX4 attains transcriptional activating capacity through a conserved DUX4 recruitment of p300/CBP, which induces histone H3 acetylation to enable target gene activation (Choi et al, 2016;Bosnakovski et al, 2021). Consistent with this, we and others have observed that global CIC::DUX4 binding overlaps with H3K27ac marks in patient derived CIC::DUX4 cell lines, again suggesting that p300/CBP may in part confer activating capacity (Thomas et al, 2023;Bakaric et al, 2024). Collectively, CIC co-opts the activating capacity of the p300/CBP associated transcription factor, DUX4, to upregulate key target genes including PEA3 family members, cell cycle genes such as CCND2 and CCNE1, and negative MAPK regulators including DUSP4 and DUSP6 that drive malignant phenotypes in aggressive undifferentiated round cell sarcomas (Kawamura-Saito et al, 2006;Yoshimoto et al, 2017;Okimoto et al, 2019;Ponce et al, 2022).…”
Section: Molecular Characteristics Of Cic Fusionssupporting
confidence: 81%
“…One limitation of interpreting this finding is that not all target genes responded to the same degree, with some maintaining baseline levels following C1-deleted CIC::DUX4 expression while others were significantly upregulated relative to EV conditions. One possible explanation for this depends on recent findings by our group and others that CIC and CIC::DUX4 may additionally bind non-canonical sites on DNA in addition to the preferred octamer ( 23 , 39 , 45 , 46 ). If the C1 domain is playing a role in binding DNA in CIC::DUX4, which seems highly likely, then its loss may differentially impact binding to target genes with variable binding motifs in their respective regulatory elements.…”
Section: Discussionmentioning
confidence: 99%